Methods and means of deanonymization of transactions in blockchain - Dubina, V.V.; Oliynykov, R.V. (Radiotekhnika, 2021)
This paper presents the results of a study of the properties of transactions formation and processing of in blockchain systems, aimed to identify existing barriers to the secure functioning of the network, processing and transmission of data between users, and to determine possible means of deanonymizing transactions. The anonymity of the network is one of the reasons for cryptocurrencies popularity and widespread use of blockchain technology. However, its presence is the basis for unscrupulous transactions, criminal actions of fraudsters and attacks on the system. Therefore, one of the main issues today is to ensure the reliable storage of information and the ability to track suspicious activity and timely protection of users in blockchain systems. The article examines known methods of increasing anonymity and maintaining confidentiality in modern networks based on the principles of blockchain technology, the threats arising from their use and the possible ways of tracking the actions of system participants. A comparative description of known tracking tools and possible means of de-anonymization of the history of completed transactions is given. As a result of the study, it was proposed to use a separate platform to analyze the network in real time, identify threats and their timely elimination, with the ability to visualize relationships and build address graphs as a result of tracking the entire chain of transactions. The tool makes it possible to implement a search among cryptocurrency addresses, blocks, transactions and tags, as well as to identify clusters associated with a particular address. The system analyzes the network in real time to gain insight into the statistics. Particular attention is paid to detecting so-called anomalies, i.e., the identification of transactions that deviate from standard structures. This allows identifying and tracking potentially malicious activities at an early stage.